Phenolic content and bioactivity of two sour cherry cultivars and their products - Kazazić, Maja; Mehić, Emina; Đapo-Lavić, Maida (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Bioactive compounds are produced as secondary metabolites in plants. Positive correlation between presence of bioactive compounds and health benefits of plants have been reported in many studies. Sour cherry contains high content of bioactive compounds, mostly polyphenols and anthocyanins. They are mostly consumed in fresh state, but are also used to produce jam, jelly, marmalade, juice, and syrup. Aim of this study was to evaluate total phenolic content, anthocyanins, as well as the antioxidant activity in two sour cherry cultivars and their products, jams and juice, prepared using traditional recipes. Total phenolic content was determined using Folin-Ciocalteu method and antioxidant activity was assessed using ABTS radical cation decolorization assay. pH-Differential method was used to determine anthocyanin content. Marasca cultivar had higher content of phenols, anthocyanins and antioxidant activity than Oblačinska cultivar. Processing of sour cherries had a greater impact on the reduction of anthocyanin content but did not have significant effect on antioxidant activity.